Effect of Emotional Intelligence on Psychological Distress: Moderating Role of Adverse Childhood Experiences amongst the University Students of Pakistan - Mustafa, Adan bint E; Ali, Rida; Ejaz, Mariam; Ejaz, Amnah (ACADEMIA International Journal for Social Sciences, 2025)
This article gives a detail information on the relationship between emotional intelligence and psychological distress keeping in mind the moderating role of adverse childhood experiences. The respondents were the university students of Pakistan from various universities across the four provinces. A sample size was 430. Validated scales were used for this study and permission was taken from the authors. The outcomes proved that relationship between the emotional intelligence and psychological distress is strengthened by the adverse childhood experiences. This study will help the university policy makers to improve the mental health policies of the students. It will also help to identify the increase of psychological distress due to the early childhood experiences.